Physicochemical, morphological and functional characteristics of starch isolated from Quercus ilex and Quercus coccifera - Lassoued , Rabeb; Abderrabba , Manef; Mejri , Jamel; Benahmed , Wafa Najar; Benhmed, Aymen; Ferhi, Mounir (Emirates Journal of Food and Agriculture, 2023)
The present research work examined and compared the morphological, physicochemical and functional characteristics extracted from two oak varietiesgrowing inTunisia. Among the findings, it was observed that Quercus ilex's starch granules had the the hightest value of lipid and phosphor content. When observed under scanning electron microscopy, both Quercus ilex and Quercus coccifera starch granules exhibited various shapes such as ovoid, spherical, elliptical and irregular, with diameters ranging from 4 to 25 µm. As for the X-ray diffraction patterns, acorn starch from both varieties displayed an A-type pattern. Comparing the properties, Quercus coccifera acorn starch exhibited higher values for the light transmittance values, the solubility, the swelling power and the gelatinization temperatures than Quercus ilex acorn starch. However, the transition enthalpy of Quercus coccifera acorn starch was the lowest among the studied parameters. These results indicate that these properties are significantly (p<0.05) different depending on the oak variety. Thus, the starches of Quercus ilex and Quercus coccifera could play different roles in various industrial applications. Keywords: acorn, functional properties starch,Quercus,physicochemical properties